2016
DOI: 10.5125/jkaoms.2016.42.3.169
|View full text |Cite
|
Sign up to set email alerts
|

A little-known relationship between immune recovery syndrome and herpes zoster

Abstract: Following anti-retroviral therapy (ART) or highly active antiretroviral therapy, there is an increased response to latent infections such as herpes zoster, which may lead to their reactivation. This is a result of improved immunity brought about by ART, also termed immune recovery syndrome. A 75-year-old male patient arrived at our institute with widespread vesicles and scabs on the right half of his face and oral cavity, suggesting the involvement of the trigeminal nerve. The patient had a history of being on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In addition to age, people in an immunosuppressive state, such as bone marrow transplant recipients and HIV-positive patients are also at risk 2,5,10 . Some authors recommend that, regardless of the concomitant presence of other risk factors, all patients with herpes zoster should be tested for HIV 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to age, people in an immunosuppressive state, such as bone marrow transplant recipients and HIV-positive patients are also at risk 2,5,10 . Some authors recommend that, regardless of the concomitant presence of other risk factors, all patients with herpes zoster should be tested for HIV 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In the first, symptoms such as pain, tingling and itching of the skin, on the distribution of the affected nerve, usually precede the rash, present in the active stage, for a few hours or several days 2 . During this period, if the branches of the trigeminal nerve are affected, tooth pain and pulp necrosis may occur, with significant diagnostic difficulties 3,4,7 . HZ should always be considered in the differential diagnosis of patients with atypical tooth pain 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An Indian study reported that 37.7% of cases with HZ also had HIV. HIV testing is suggested for patients younger than 50 years of age or those who present with more than one dermatomal involvement ( Bhandage et al, 2016 ).…”
Section: Infectionsmentioning
confidence: 99%